Epistemologi Pendidikan Qur’ani: Sumber, Metode, dan Tujuan Pendidikan dalam Al-Qur’an - Ahmad Sudi (Advances In Education Journal, 2025)
This study examines the epistemology of Qur’anic education by analyzing the sources, methods, and objectives of education as articulated in the Qur’an. The research addresses the epistemological problem of fragmentation between revelation-based knowledge and rational-empirical approaches in contemporary Islamic education. The aim of this study is to formulate a comprehensive epistemological framework of Qur’anic education that integrates revelation, reason, and empirical reality. This research employs a qualitative library-based method, using content analysis of Qur’anic verses related to education, supported by classical and contemporary Islamic educational literature. The findings indicate that Qur’anic epistemology positions revelation as the primary source of knowledge, supported by reason and empirical observation as complementary instruments. Educational methods emphasized include reflection (tadabbur), intellectual inquiry (tafakkur), and exemplary practice (uswah). The study concludes that Qur’anic education aims to form individuals who are spiritually grounded, morally upright, intellectually competent, and socially responsible. This epistemological model offers a holistic foundation for reforming contemporary Islamic education.